2020
DOI: 10.1111/1750-3841.15299
|View full text |Cite
|
Sign up to set email alerts
|

Bovine skin gelatin hydrolysates as potential substitutes for polyphosphates: The role of degree of hydrolysis and pH on water‐holding capacity

Abstract: The effects of adding bovine skin gelatin hydrolysate obtained with subtilisin, on water‐holding capacity (WHC), in a thermally processed chicken meat model, were investigated. Hydrolysates with different degrees of hydrolysis (DH) (6.57%, 13.14%, and 26.28%) were prepared. The results showed that all the tested hydrolysates improved water retention in the meat matrix. The hydrolysate with 26.28% DH showed similar behavior throughout the full range of concentrations [0% to 5% w/w] compared to that of the posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
2
13
2
Order By: Relevance
“…However, several studies have shown that the type of enzyme used to breakdown collagen protein can influence the DH effectiveness. The use of the enzyme subtilisin in gelatin hydrolysates from bovine skin showed lower DH compared to our data (6.57%) (Nuñez et al, 2020). Furthermore, the use of pepsin, papain, and protease enzymes increased the DH in fish collagen by 10, 20, and 28%, respectively (Hema et al, 2017).…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…However, several studies have shown that the type of enzyme used to breakdown collagen protein can influence the DH effectiveness. The use of the enzyme subtilisin in gelatin hydrolysates from bovine skin showed lower DH compared to our data (6.57%) (Nuñez et al, 2020). Furthermore, the use of pepsin, papain, and protease enzymes increased the DH in fish collagen by 10, 20, and 28%, respectively (Hema et al, 2017).…”
Section: Resultscontrasting
confidence: 78%
“…However, several studies have shown that the type of enzyme used to breakdown collagen protein can influence the DH effectiveness. The use of the enzyme subtilisin in gelatin hydrolysates from bovine skin showed lower DH compared to our data (6.57%) (Nuñez et al, 2020).…”
Section: Ta B L E 1 Physicochemical Analysis Of Commercial Collagen H...contrasting
confidence: 90%
“…These results are in consistent with the finding of (Mudgil et al ., 2019b) who have reported an increase in DH with the time of hydrolysis from 2–6 h in camel skin gelatin hydrolysates. (Nuñez et al ., 2020) reported that at E/S ratio (1:4) for 24 h, bovine gelatin‐derived hydrolysate produced by subtilisin demonstrated highest DH (26.28% ± 1.21%). Protease (P) and a combination of protease and alcalase (AP) were the most effective enzymes for hydrolysing CSG to shorter peptides, as evidenced by higher DH than alcalase (A) alone ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In general, high WHC of the added component can resist water losses, keep weight, and quality of bakery food (Kotoki & Deka, 2010). Moreover, WHC of meat product can also be enhanced by mixing with protein binders, owing to water affinity of the binders (Colle et al., 2019; Nuñez et al., 2020).…”
Section: Resultsmentioning
confidence: 99%